Hadis-Hadis dalam Buku-Buku Kumpulan Teks Khutbah: Studi tentang Struktur Periwayatan Hadis: Hadiths in Sermon Text Anthologies: A Study of the Structure of Hadith Transmission - Saefuddin Saefuddin (Fenomena, 2004)
The widespread circulation of Friday sermon textbooks in Muslim society contrasts with the authors' failure to adhere to hadith transmission standards from the perspective of ulum al-hadith. The transmission structure—comprising the narrator (rawi), text (matan), and chain of transmission (sanad)—is essential for assessing hadith authenticity. This study analyzes the extent to which sermon textbook authors fulfill these three elements, particularly by presenting complete sanads and mentioning narrators or mukharrij. Using a qualitative approach with rational-reflective reasoning and content analysis of 808 hadiths from ten sermon textbooks, the findings reveal that nearly 90% of hadiths lack complete sanads, and 64.8% do not mention the rawi or mukharrij. Only one author, Muhammad Al-Ghazali, provided complete references through footnotes. The study concludes that most authors fail to meet the requirements of the hadith transmission structure. It recommends that sermon textbook authors either cite the complete sanad or refer to primary hadith collections via footnotes. Fenomena maraknya buku teks khutbah Jumat di masyarakat tidak disertai dengan kepatuhan penulis terhadap kaidah periwayatan hadis dalam perspektif ulumul hadis. Padahal, struktur periwayatan yang terdiri atas rawi, matan, dan sanad merupakan elemen krusial untuk menilai keotentikan hadis. Penelitian ini bertujuan untuk menganalisis sejauh mana penulis buku teks khutbah memenuhi ketiga unsur tersebut, khususnya dalam penyebutan sanad secara utuh dan pencantuman nama rawi atau mukharji. Metode yang digunakan adalah pendekatan kualitatif dengan pola pikir reflektif rasionalistik serta analisis isi terhadap 808 hadis yang termuat dalam sepuluh buku teks khutbah. Hasil penelitian menunjukkan bahwa hampir 90% hadis tidak menyebutkan sanad secara lengkap, dan 64,8% tidak menyebutkan rawi atau mukharji. Hanya satu penulis, Muhammad Al-Ghazali, yang mencantumkan rujukan lengkap melalui catatan kaki. Kesimpulannya, mayoritas penulis belum memenuhi tuntutan struktur periwayatan hadis. Penelitian ini merekomendasikan agar penulis buku teks khutbah menyebutkan sanad secara lengkap atau merujuk pada kitab induk hadis melalui catatan kaki.